2008
DOI: 10.1128/aem.01616-07
|View full text |Cite
|
Sign up to set email alerts
|

Parameters Affecting Ethyl Ester Production bySaccharomyces cerevisiaeduring Fermentation

Abstract: Volatile esters are responsible for the fruity character of fermented beverages and thus constitute a vital group of aromatic compounds in beer and wine. Many fermentation parameters are known to affect volatile ester production. In order to obtain insight into the production of ethyl esters during fermentation, we investigated the influence of several fermentation variables. A higher level of unsaturated fatty acids in the fermentation medium resulted in a general decrease in ethyl ester production. On the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
267
2
11

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 415 publications
(311 citation statements)
references
References 40 publications
31
267
2
11
Order By: Relevance
“…Excess amount of ethyl esters could impart waxy and soapy notes to wine, and mixed-culture by selecting optimal fermentation time could mitigate ethyl ester production. It was reported that the relative concentration of fatty acid precursors was the limiting factor for ethyl ester production (SAerenS et al, 2008). Thus, the low production of ethyl esters in the monoculture of W. mrakii was probably due to its lower level of fatty acid precursors.…”
Section: Evolution Of Volatilesmentioning
confidence: 99%
“…Excess amount of ethyl esters could impart waxy and soapy notes to wine, and mixed-culture by selecting optimal fermentation time could mitigate ethyl ester production. It was reported that the relative concentration of fatty acid precursors was the limiting factor for ethyl ester production (SAerenS et al, 2008). Thus, the low production of ethyl esters in the monoculture of W. mrakii was probably due to its lower level of fatty acid precursors.…”
Section: Evolution Of Volatilesmentioning
confidence: 99%
“…(Saerens et al, 2008). The concentrations of ethyl esters were higher than their threshold levels ( Table 2).…”
Section: Figurementioning
confidence: 99%
“…They are synthesized by the grapes but are also produced by yeasts in course of alcoholic fermentation [55]. During malolactic fermentation, significant changes in the concentration of individual esters were observed [56].…”
Section: Esterhydrolases and -Synthetasesmentioning
confidence: 99%